Optimalisasi Sistem Pembayaran Digital yang Mudah dan Aman dalam E-Commerce: Tinjauan Hukum Bisnis - Rifqi Febrianto; Sri Agustiani; Zeni Yanuariska (Program Studi Ilmu Hukum, Universitas Kuningan, 2025)
In line with the rapid development of technology, payment patterns and systems in economic transactions continue to change. Technological advances in payment systems have shifted the role of cash (currency) as a means of payment into a more efficient and economical form of digital payment. The presence of non-cash payment instruments is not only caused by innovation in the banking sector but is also driven by the public's need for a practical payment instrument that can provide convenience in making transactions. This paper aims to examine the optimization of digital payment systems in e-commerce transactions from a business law perspective. The main focus of this study includes an analysis of applicable regulations, consumer protection, and efforts to mitigate the risk of cybercrime in digital transactions. The method used in this paper is qualitative and supported by a phenomenological approach. Digital payment systems have advantages and disadvantages. But in general, the advantages of digital payment systems outweigh their disadvantages. The presence of this digital payment system does not mean eliminating the existence of cash. However, the existence of this digital payment system can also minimize inflation due to the large amount of money circulating in the community.